Hospitality in Islam as Based on Cornille's Conditions for Constructive Interreligious Dialogue - Duderija, Adis (Journal of ecumenical studies, 2017)
This essay employs Catherine Cornille's conditions for a constructive interreligious dialogue theoretical framework with reference to the Islamic tradition as exemplified by the work of Reza Shah-Kazemi, a contemporary proponent of Islamic mysticism and the Islamic branch of religio perennialis. More specifically, it demonstrates how Cornille's "commitment," "interconnection," and "hospitality" conditions for constructive interreligious dialogue are very present in the Islamic tradition.